Epidermolysis Bullosa Simplex Superficialis (EBSS) Mimicking Peeling Skin Syndrome - Gharami R C; Mandal M K; Patra A C (Wolters Kluwer Medknow Publications, 2002)
A five year old girl with EBSS Presented with vesicular lesions, followed by peeling of skin since the age of two months.